Carbon and Lipid Contents of the Copepod Calanus finmarchicus Entering Diapause in the Fram Strait and Their Contribution to the Boreal and Arctic Lipid Pump - Tarling, Geraint A.; Belcher, Anna; Blackwell, Mayleen; Castellani, Claudia; Cook, Kathryn Barbara; Cottier, Finlo R.; Dewar-Fowler, Victoria; Freer, Jennifer J.; Gerrish, Laura; Johnson, Magnus L.; Last, Kim S.; Lindeque, Penelope Kate; et al. (Frontiers in Marine Science, 2022)
The boreal copepod Calanus finmarchicus sequesters substantial amounts of carbon (C) in the deep layers of the North Atlantic Ocean through their contribution to the “lipid pump.” This pump is driven by these zooplankton descending from the surface layers to spend prolonged periods at depth during which time they metabolise substantial lipid reserves and a fraction suffer mortality. C. finmarchicus is principally a boreal species but is expatriated by currents flowing northwards into Arctic regions such as the Fram Strait, where it is now able to complete its life cycle. We considered how this expansion to its distributional range adds to the estimated magnitude of the lipid pump. Field sampling in the Fram Strait found C. finmarchicus abundance to be spatially variable with high values, equivalent to those reported for core distributional areas further south, found mainly in the eastern region. Lipid reserve levels were sufficient for many individuals to survive the overwintering period and reproduce the following spring. In accordance with abundance patterns, lipid pump magnitude was greater in the Eastern Fram Strait (2.04 g C m−2 year−1) compared to the Western Fram Strait (0.33 g C m−2 year−1). At least for the eastern region, these rates are similar to those reported for this species elsewhere (average of 4.35 g C m−2 year−1). When extrapolated to the wider spatial area of the Fram Strait, the lipid pump generated by this species in this ocean sector amounts to 0.3 Mt C year−1. Although constituting a modest proportion of the total C. finmarchicus lipid pump of 19.3 Mt C year−1, it indicates that the continued northwards expansion of this species will act to increase the size of its lipid pump, which may counteract that lost through the northwards retreat of its Arctic congeners, Calanus glacialis and Calanus hyperboreus.